The Effectiveness of â€œLearn Socialâ€ Platform for Studentsâ€™ Writing Skill at Universitas Sumatera Utara - Situmorang, M. Rizky Unedo; Sofyan, Rudy; Sumbayak, Desri Maria (Politeknik Harapan Bangsa Surakarta, 2022)
The study attempts to find out the effectiveness of an online learning platform provided by the English Department language center at Universitas Sumatera Utara regarding to the English Literature class of 2018 students’ writing skill. The thesis was conducted by analyzing the result of the questionnaire given to the students via google form. The research used the qualitative descriptive method and the indicators proposed by Slavin. Based on the questionnaire result, it showed that Learn Social online platform is effective for students’ writing skill. It is shown through the students’ feedback by answering the questionnaire where the result is positive. The indicators used in order to measure the effectiveness of the online platform are instruction, the appropriate level of instruction, incentive, and time where all four of the indicators get a positive result.